Implementasi Standar Industri Hijau pada Industri Penyamakan Kulit - 10070219055, Zamzam Imanudin; Aviasti; Amaranti, Reni (UNISBA Press, 2024)
Abstract. PT Elco Indonesia Sejahtera has several environmental problems resulting from leather tanning activities, especially the beamhouse process, such as liquid waste that pollutes rivers, unpleasant odors in the environment around the company, dirty and smelly production areas, environmental pollution, and accumulation of solid waste around the company. This phenomenon arises because companies do not have standard work procedures for the beamhouse process and management of other aspects such as raw materials, chemicals, packaging materials, energy and water use, and waste management. The aim of this research is to design Standard Operating Procedures (SOP) as a reference for implementing Green Industry Standards in the PT Elco beamhouse process. The research was carried out by observation and interviews with the company. Based on the results of a comparison of the company's SIH compliance with the seven aspects contained in the regulation, it is known that the operational feasibility of implementing the PT Elco Green Industry Standard is not feasible. The percentage of fulfillment of aspects of raw materials, chemicals, packaging materials, beamhouse processes, use of electrical energy and water, waste management is 0% or no indicators are met. Meanwhile, in the liquid waste management aspect, the SIH percentage is 50%. Therefore, from this data it is necessary to design SOPs for all aspects so that they can be used as a reference by companies in implementing Green Industry Standardization Abstrak. PT Elco Indonesia Sejahtera memiliki beberapa permasalahan lingkungan yang dihasilkan dari aktivitas penyamakan khususnya proses beamhouse seperti limbah cair yang mengotori sungai, bau yang tidak sedap di lingkungan sekitar perusahaan, area produksi yang kotor dan bau, pencemaran lingkungan, serta penumpukan limbah padat di sekitar perusahaan. Fenomena tersebut muncul dikarenakan perusahaan tidak memiliki prosedur kerja yang baku pada proses beamhouse dan pengelolaan aspek-aspek lain seperti aspek bahan baku, bahan kimia, bahan kemasan, penggunaan energi dan air, serta pengelolaan limbah. Tujuan dari penelitian ini untuk merancang Standar Operasional Prosedur (SOP) sebagai acuan penerapan Standar Industri Hijau untuk proses beamhouse PT Elco. Penelitian dilakukan dengan observasi dan wawancara terhadap pihak perusahaan. Berdasarkan hasil penelitian pemenuhan SIH perusahaan dengan tujuh aspek yang terdapat dalam regulasi, diketahui bahwa kelayakan operasional penerapan Standar Industri Hijau PT Elco tidak layak. Persentase pemenuhan untuk aspek bahan baku, bahan kimia, bahan kemasan, proses beamhouse, penggunaan energi Listrik dan air, pengelolaan limbah padat bernilai 0% atau tidak terdapat indikator yang terpenuhi. Sedangkan pada aspek pengelolaan limbah cair pemenuhan persentase SIH sebesar 50%. Maka dari data tersebut, diperlukan perancangan SOP pada keseluruhan aspek agar dapat dijakan acuan oleh perusahaan untuk menerapkan Standarisasi Industri Hijau